The Singapore Convention on Mediation a commentary - Alexander, Nadja Marie, 1966- (Kluwer Arbitration., 2019)
The Singapore Convention on Mediation is just beginning its life as an international legal instrument. How is it likely to fare? In this first comprehensive, article-by-article commentary, the authors provide a robust report on the features of the Convention and their implications, with analysis of potential controversies and authoritative clarifications of particular provisions.